Trends of the Iraqi drama between the domination of funding and production problems: An analytical study of the 2020 Ramadan series - Shatha Hussein Mohammed; Dr. Inas AbdulHafedh Ahmed (Genius Journals, 2022)
The subject of Iraqi drama in Ramadan formed a big controversy between the technical and social media. Therefore, this study addressed the trends of Iraqi drama between the domination of funding and production problems. It aimed at highlighting the real problems that provoked controversy on the television series shown in the 2020 Ramadan on Iraqi and Arab satellite channels. In addition to clarifying how funding imposes ideas on dramatic texts in television broadcasts, whether in television series or programs in general. It also aimed at explaining how satellite channels can change the contents of programs according to the policy of the broadcast channel or according to the funding. It reviewed the effects of modern techniques in production methods on the recipients and their awareness and ideas, as well as the political funding that enters the production companies and tries to change ideologies and facts or falsify them.
Keywords: Iraqi drama; social media; study; Ramadan